Industrial wastewater treatment for fertilizer industry a case study - Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ranade, Vivek V. (Desalination and Water Treatment, 2016)
Wastewaters from chemical fertilizer industry mainly contain organics, alcohols, ammonia, nitrates, phosphorous, heavy metals such as cadmium and suspended solids. The nature of effluent streams varies in terms of its constituents and complexity. The present work attempts to fill the void in the literature that mostly reports synthetic wastewater treatment studies, by evaluating effluent treatment solutions and comparison of different methods for real wastewaters from the fertilizer industry. An attempt has been made to devise suitable methodology mainly using a new device in the form of vortex diode for hydrodynamic cavitation and also using adsorption, for several real wastewater streams from different locations in one major fertilizer industry of Maharashtra, India. The strategy involved characterization of wastewaters, studies on the effective removal of chemical oxygen demand (COD) and devising solutions for effective reduction in ammoniacal nitrogena more serious issue in the fertilizer industry. The characterization of wastewaters from different streams revealed huge variation in COD from 50 to 140,000ppm and ammoniacal nitrogen from 6 to 1,700ppm. Some effluent streams contained alcohol up to 5%. Hydrodynamic cavitation using vortex diode and adsorption with modified carbons were used to treat these streams. Cavitation studies were carried out on a pilot plant and the effect of pressure drop, cavitating device and process intensification were studied. It was observed that the effluent treatment strategy requires careful identification and application of suitable treatment method on the basis of the nature of the effluent. Also, hydrodynamic cavitation, using vortex diode appears to be techno-economically attractive option in treating fertilizer wastewaters giving a very high reduction in COD and ammoniacal nitrogen (up to 85%), similar to adsorption. The results clearly identify potential of newer methodologies in the treatment of effluents in the fertilizer industry.

Improving efficiency for removal of ammoniacal nitrogen from wastewaters using hydrodynamic cavitation - Patil, Pravin B.; Bhandari, Vinay M.; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2021)
The present study reports significant improvements in the removal of ammoniacal nitrogen from wastewater which is an important problem for many industries such as dyes and pigment, distilleries and fisheries. Pilot plant studies (capacity, 1 m(3)/h) on synthetic wastewater using 4-amino phenol as model nitrogen containing organic compound and two real industrial effluents of high ammoniacal nitrogen content were carried out using hydrodynamic cavitation. Two reactor geometries were evaluated for increased efficiency in removal-orifice and vortex diode. Effect of initial concentration (100-500 mg/L), effect of pressure drop (0.5-5 bar) and nature of cavitating device (linear and vortex flow for cavitation) were evaluated along with effect of salt content, effect of hydrogen peroxide addition and aeration. Initial concentration was found to have significant impact on the extent of removal: similar to 5 g/m(3) removal for initial concentration of 100 mg/L and up to 12 g/m(3) removal at high concentration of 500 mg/L. Interestingly, significant improvement of the order of magnitude (up to 8 times) in removal of ammoniacal nitrogen could be obtained by sparging air or oxygen in hydrodynamic cavitation and a very high removal of above 80% could be achieved. The removal of ammoniacal nitrogen by vortex diode was also found to be effective in the industrial wastewaters and results on two different effluent samples of distillery industry indicated up to 75% removal, though with longer time of treatment compared to that of synthetic wastewater. The developed methodology of hydrodynamic cavitation technology with aeration and vortex diode as a cavitating device was found to be highly effective for improving the efficiency of the conventional cavitation methods and hence can be highly useful in industrial wastewater treatment, specifically for the removal of ammoniacal nitrogen.
Keywords: Amino phenol; Cavitation; Oxidation; pollution; Wastewater treatment

Intensified hydrodynamic cavitation using vortex flow based cavitating device for degradation of ciprofloxacin - Patil, Pravin B.; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2022)
The present work, for the first time, establishes degradation behavior of ciprofloxacin (CIP), a widely used fluoroquinolone group of antibiotics, using vortex flow based hydro-dynamic cavitation (HC) for low to high concentrations of CIP (10 and 100 mg/L). Effect of pressure on the degradation of CIP and TOC reduction was investigated on pilot plant scale (capacity 1 m3/h). Process intensifications using aeration as well as hydrogen per-oxide (H2O2) were also investigated. While aeration did not yield any significant en-hancement, process intensification using H2O2 resulted in similar to 200% enhancement in the CIP degradation as compared to HC alone. Excellent degradations, to an extent of 79 & 95%, were achieved corresponding to high cavitational yields of 7.2 x 10-4 mg/J and 86.8 x 10-4 mg/J for CIP concentrations of 10 and 100 mg/L respectively using the process intensified approach of HC and H2O2, not reported so far for cavitating devices without moving ele-ments. The developed methodology demonstrated 4-7 times improvement in per-pass degradation and low cost with high efficiency compared to the conventional cavitation. The results clearly highlight utility of the process intensified approach using H2O2 for the degradation of CIP even at high concentrations, specifically important for pharmaceutical industries requiring zero liquid discharge norms.(c) 2022 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Antibiotics removal; ciprofloxacin; Degradation; Oxidation; Wastewater treatment

Improving hydrodynamic cavitation using newer surface-coated cavitation reactors - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2023)
Surface-coated cavitation devices, vortex diode (SCVD) have been reported for the first time for enhancing efficiency of hydrodynamic cavitation (HC). Two surface-coated cavitation reactors using coating of copper and nickel (-50 mu m) were evaluated, also comparing results with conventional reactor vortex diode. The proof of concept is successfully demonstrated for complete degradation of two model organic pollutants, antibioticscephalexin (CFX) and ciprofloxacin (CIP). The surface-coated reactors provide dual activity, and the catalytic effect is highly pronounced with process intensification using H2O2 and/ or pH alternations. Integration of SCVD, pH and H2O2 was the most effective strategy. Complete degradation of the antibiotics was achieved within minutes with H2O2 (-1000 molar ratio) for both Cu and Ni-surface-coated cavitation reactors compared to lower degradation of-19% for CFX and-37% for CIP using only HC. An excellent enhancement of over 300% for CFX degradation at pH 11 and-170% for CIP degradation at pH 4 was obtained. Huge enhancements in per-pass degradation and cavitational yields (up to 400 times) clearly highlight the utility of the surface-coated cavitation reactors in various applications and for cost-effectiveness.(c) 2023 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrodynamic cavitation; Oxidation; pollution; Reactor; Technology; Wastewater treatment